Changes in Condition Factor, Hepatosomatic and Gonadosomatic Index of Yellowfin Tuna (Thunnus albacares) in Captivity - Jhon Harianto Hutapea; Ananto Setiadi; Gunawan Gunawan (Universitas Gadjah Mada, 2022)
The necessity for tuna products in the world community continues to increase, while production relies only on catching, thus causing overfishing. Therefore, breeding technology to support tuna farming is fundamental to be developed. Yellowfin tuna farming in Indonesia has been successful in cultivating broodstock. This paper discusses biometric data that changes during cultivation, such as condition factor, hepato and gonadosomatic indexes compared with wild captured. Data were collected from young tuna to broodstock and compared with wild captured such as fork length, body, liver and gonad weight. The condition factor (K) of cultivated tuna (1.5-2.5) was higher compared with wild captured (1.5-2.0). Similarly, the value of cultivated tuna’s hepatosomatic index (HSI) was higher (0.63-1.14). In contrast, the gonadosomatic index (GSI) of wild captured yellowfin tuna was higher (>0.5) compared with cultivated yellowfin tuna in a circular concrete tank (0.4) but lower than that cultivated in a floating net cage (>1.4). Maintenance of broodstock in the tank with a lower GSI value means the number of eggs produced is relatively lower than its natural counterpart. At the same time, the high GSI value of cultivated broodstock in FNC shows better results than wild captured broodstock.